Determination of Fano factor and pre-amplifier noise from the measurement of energy resolution of a HPGe detector - Samat, S.B.; Priharti, W. (Universiti Kebangsaan Malaysia, 2015)
A HPGe detector and γ-ray multinuclide standard solution were used to get several data pairs of photon energy E and detector’s energy resolution FWHM. A series of graph of FWHM2 versus E was plotted to determine the detector’s Fano factor and pre-amplifier noise, which yielded the mean values of 0.123±0.003 and (7.448±0.011) × 10−1 keV, respectively. The Fano factor value agrees within 95% confident interval with the mostly quoted value of 0.13 for semiconductor detectors. The obtained preamplifier noise is in agreement with typical manufacturer’s specification.